Legal implications of utilizing geophysical methods for resource exploration and environmental protection - Mohammed Zuhair; Ameen Hadi Hassoon Ali; Israa Zaidan Khalaf Mashhoot; Bushra Abd-Al Latif Jasim; Ghanim Magbol Alwan (Environment and Social Psychology, 2025)
Geophysical techniques have emerged as indispensable tools in the field of resource exploration and environmental monitoring, providing key benefits in subsurface imaging, non-destructive surveying, and analytical decision support. But their deep adoption has also raised fundamental legal questions about regulatory clarity, environmental accountability, stakeholder rights and data reliability. We discuss legal frameworks governing geophysical techniques in a range of jurisdictions, evaluating how these frameworks balance environmental management, procedural efficiency and party equity. Through a multidisciplinary procedure, this study integrates legal evaluation, environmental impact models, stakeholder survey information, comparative jurisdictional evaluation, and geophysical data verification. Results show significant differences in the clarity and enforcement of the law between countries, with some jurisdictions having efficient and aligned regulation and others with an excessive level of red tape. (Stakeholder sentiment suggests perceptions of legal fairness are mixed at best, with landowners expressing the greatest dissatisfaction, especially in the transparency and compensation mechanisms.) Additionally, despite the relatively low-impact nature of the surveys, many measurable disturbances, particularly increased noise and vibration, suggest the need for increased environmental oversight. The analysis also highlights the critical importance of checking geophysical datasets to maintain a scientific standard in regulatory or legal contexts. The conclusion of this study highlights the need for legal evolution to keep pace with technological evolution, through clearer rules, standards harmonization and data quality protocols. This requires amendments to regulations to enable responsible exploration, promote environmental sustainability, and ensure equitable stakeholder engagement in the governance of geophysical activities.